Formation of Surface Ultrafine Grain Structure and Their Physical and Mechanical Characteristics Using Vibration-Centrifugal Hardening - Volodymyr Kyryliv; Yaroslav Kyryliv; Nataliya Sas (Advances in Materials Science and Engineering)
The vibration-centrifugal hardening forms a gradient ultrafine grain structure of the ferritic class with a grain size of 190 nm and a surface microhardness of 8.9 GPa and a depth of up to 6 mm on the surface of 40 Kh steel of the ferritic-pearlitic structure. These parameters are formed due to an increase in the mass of the tool that acts on the processed surface through the balls and depend on the treatment modes. This surface ultrafine grain structure increases the wear resistance properties of steel in oil and oil-abrasive environment and improves the electrochemical characteristics.